An examination of the bleeding complications associated with herbal supplements, antiplatelet and anticoagulant medications. - Spolarich AE; Andrews L (Journal of Dental Hygiene)
Dental professionals routinely treat patients taking prescription, nonprescription, and herbal medications that are known or have the potential to alter bleeding. Prescription anticoagulant and antiplatelet medications, as well as over-the-counter drugs such as aspirin, are typically taken to reduce the risk of thromboembolic events, including stroke. Herbal supplements are widely used for a variety of indications, and both patients and health care practitioners are often unaware of the anticoagulant and antiplatelet effects that occur as either predictable pharmacologic effects or adverse side effects of herbal medicines. In addition, patient use of these herbal supplements is usually undisclosed to health care providers. The purpose of this literature review is to examine the mechanisms of action of drugs and herbs that alter bleeding, and to educate dental professionals as to the proper care and management of patients using these medications. Decision-making strategies, including interpretation of laboratory tests, and when to discontinue the use of these medications are discussed. Patients undergoing routine dental and dental hygiene procedures do not need to discontinue the use of anticoagulant and antiplatelet medications. However, alterations in drug use may be required for those patients undergoing invasive surgical procedures. It is recommended that herbal supplements must be discontinued 2 weeks prior to receiving invasive surgical procedures. Dental practitioners must learn to weigh the risks of discontinuing drug therapy against the potential risks to patients, and implement risk reduction strategies to minimize adverse bleeding complications associated with dental treatment.